Impact Of Media QR Code To Grow The Interest Of Students Learn Sociology In Social Conflict Materials - Anna Rusmiyati (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2019)
The existence of innovative learning allows dynamism in learning. The presence of technology in the world of education is to help teachers and students to obtain the speed of information, create innovative learning, and facilitate all teaching and learning activities. One result of technology that can be utilized in learning is the presence of a smartphone. On the smartphone, there is a QR Code media that can be downloaded via Google Play. One of the sociological materials, namely social conflict is the choice to be presented with QR Code media. The implementation is that students from one of the groups download the QR Code on their smartphone so that they can scan the assignments given by the teacher in the form of barcodes. Previously the teacher had prepared questions about the subject of social conflict in the form of barcodes. Gurupun also download a barcode generator on a smartphone to be able to write the problem, then the final result in the form of a barcode. The results in the form of barcodes are then printed. Then students do the scanning on the printed barcode and the task or problem to appear will appear. Completion of tasks is done in groups so as to accelerate the process. Learning with QR Code media also includes 21st century educational abilities, including literacy, strengthening character education, and 4C (critical, communicative, collaborative, and creative). By using the QR Code media it turns out to be very effective in fostering students' interest in studying sociology. Keywords : Innovative learning, QR Code, Barcode Generator, Scaning, Social Conflict